2020
DOI: 10.1111/cpr.12765
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia: Versatile regulator in cartilage development

Abstract: Cartilage is a connective tissue in the skeletal system and has limited regeneration ability and unique biomechanical reactivity. The growth and development of cartilage can be affected by different physical, chemical and biological factors, such as mechanical stress, inflammation, osmotic pressure, hypoxia and signalling transduction. Primary cilia are multifunctional sensory organelles that regulate diverse signalling transduction and cell activities. They are crucial for the regulation of cartilage developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 113 publications
0
23
0
Order By: Relevance
“…There is recognizable basic science knowledge to suggest that mechanical loading of the growth plate has a significant impact on chondrocyte proliferation and hypertrophy and subsequent skeletal genesis [29][30][31][32]. These inferences apply to both physiologic and pathologic mechanical stresses.…”
Section: Discussionmentioning
confidence: 99%
“…There is recognizable basic science knowledge to suggest that mechanical loading of the growth plate has a significant impact on chondrocyte proliferation and hypertrophy and subsequent skeletal genesis [29][30][31][32]. These inferences apply to both physiologic and pathologic mechanical stresses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these experiments affected the collagenase MMP-13 (=matrix metalloproteinase 13 also known as collagenase-3) levels [62]. MMP-13 is a key protein for the cartilage matrix catabolism [63]. It is responsible for chondrocyte proliferation, cellular migration, cell apoptosis, degradation of collagen II, alterations of the ECM and the cartilage to bone transformation [64].…”
Section: Links Between Primary Cilia and Tissue Organization During Smentioning
confidence: 99%
“…Thompson et al discovered that the expression of MMP-13 and ADAMTS-5 is neither dependent of Ihh nor in coexistence with IL-1β [97]. However, Tao et al showed disturbed ciliary function via knock out of the ciliary motor protein Kif3a in mice leads to altered MMP-13 levels [63]. He et al described another PC-associated signaling pathway that leads to increased MMP-13 and MMP-1 levels.…”
Section: Molecular Links Between Pc and Osteoarthritismentioning
confidence: 99%
“…The primary cilium is a non-motile, microtubule-supported organelle that often projects outward from the cell surface, allowing sensation of the mechanical environment ( Singla and Reiter, 2006 ; Malone et al, 2007 ; Deren et al, 2016 ; Spasic and Jacobs, 2017b ). It is present on diverse cell types in developing and mature tissues and has been studied during organogenesis of the kidneys, nervous system, heart, and skeleton (reviewed in Gerdes et al, 2009 ; Fry et al, 2014 ; Tao et al, 2020 ). The membrane encapsulating the cilium axoneme is distinct from the adjacent cellular membrane, with localized membrane-bound receptors and other cilium-specific proteins (reviewed in Jensen and Leroux, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cilia are vital to correct Hh signaling in the limb buds of mouse and chick embryos, leading to misspecification of digits and polydactyly when cilia are absent or non-functional ( Bangs et al, 2011 ). The absence of cilia from mesenchymal condensations (under Dermo1-Cre) or cartilage (Col2aI-Cre), or global mutations of ciliary genes, result in limb shortening, disorganized chondrocytes, craniofacial abnormalities, hypomineralization, and dwarfism, suggesting altered cell signaling that impacts skeletal differentiation ( Koyama et al, 2007 ; Song et al, 2007 ; Tao et al, 2020 ). Yuan and Yang (2015) showed that primary chondrocytes derived from postnatal cilia-deficient mice had deficient Hh signaling and enhanced responsiveness to canonical Wnt signals.…”
Section: Introductionmentioning
confidence: 99%